2007
DOI: 10.2460/ajvr.68.9.995
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and enzymatic characterization of purified covalent complexes of matrix metalloproteinase-9 and haptoglobin released by bovine granulocytes in vitro

Abstract: A fraction of neutrophil MMP-9 is released in complex with haptoglobin. The complex is present in granules and retains biological activity of its components. Detection of the complex in serum may provide an indicator of acute inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Bannikov et al (2007) reported that neutrophil MMP-9 is covalently complexed with neutrophil synthesized Hp suggesting that this is a potentially useful biomarker indicating activation and degranulation of neutrophils (Theurer et al, 2013). Increases in plasma Hp-MMP-9 concentration over time are consistent with other studies reporting significantly elevated plasma Hp-MMP-9 concentrations in cattle with acute inflammation (Bannikov et al, 2011).…”
Section: Haptoglobin-matrix Metalloproteinase-9 Complexessupporting
confidence: 81%
“…Bannikov et al (2007) reported that neutrophil MMP-9 is covalently complexed with neutrophil synthesized Hp suggesting that this is a potentially useful biomarker indicating activation and degranulation of neutrophils (Theurer et al, 2013). Increases in plasma Hp-MMP-9 concentration over time are consistent with other studies reporting significantly elevated plasma Hp-MMP-9 concentrations in cattle with acute inflammation (Bannikov et al, 2011).…”
Section: Haptoglobin-matrix Metalloproteinase-9 Complexessupporting
confidence: 81%
“…34 Complexes of MMP-9 and Hp have been detected in sera of cows with acute inflammation, but not in clinically normal cows or cows with chronic disease. 35 The interaction between Hp and MMP in aneurysm development has not been fully investigated. A functional study performed by de Kleijn et al revealed that Hp inhibits the activity of MMP-2 by 50% and MMP-9 by 30% in cultured arterial smooth muscle culture cells, but increases the production of gelatin in arterial smooth muscle cells in Hp knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous work, we demonstrated that phorbol ester stimulation of isolated peripheral blood neutrophils are is associated with appearance of Hp-MMP 9 complexes in culture medium within 30 minutes [22]. We also identified covalent, heteromeric complexes of Hp in complex with matrix metalloproteinase 9 (Hp-MMP 9), within the serum of cattle with clinically apparent acute onset of septic inflammation of the abdomen or thorax [23].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to free serum Hp, whose main source is the liver during inflammation, serum Hp-MMP 9 complexes are only produced by neutrophils. As such, Hp-MMP 9 complexes, in serum, represent neutrophil degranulation [22]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation